Sequestration of crystal violet dye from wastewater using low-cost coconut husk as a potential adsorbent - Muhammad Sajid Imran (Water Science and Technology, 2022)
The current study explores the effectiveness of coconut husk for crystal violet dye sequestration employing a batch experimental setup. Characterization of adsorbent was carried out via FTIR, and SEM techniques and results confirmed the involvement of OMe, COC and hydroxyl functional groups in dye uptake, and the rough, porous nature of adsorbent and after adsorption dye molecules colonized these holes resulting in dye exclusion. Effects of various adsorption parameters such as pH, adsorbent dose, contact time, initial dye concentration, and temperature of solution were studied. Crystal violet adsorption on coconut husk was highly pH-dependent, with maximum removal occurring at basic pH. Maximum removal of dye, i.e., 81%, takes place at optimized conditions. Kinetic data was analyzed by pseudo-first, pseudo-second order and an intra-particle diffusion model. Results showed that the pseudo-second order kinetic model best described adsorption of crystal violet onto coconut husk. Langmuir, Freundlich, and D-R adsorption isotherms were also used to test their appropriateness to experimental data and the Freundlich isotherm fits best to data. Thermodynamic parameters showed that the current process was spontaneous, endothermic in nature with continuous decrease in entropy. Established practice is 79% applicable to tap water and in acidic medium nearly 80% of adsorbent was recovered, confirming the effectiveness and appropriateness of coconut husk for crystal violet dye exclusion from wastewater. HIGHLIGHTS Adsorption is an effective and economical process for dye removal from wastewater.; Coconut husk is a potential adsorbent for crystal violet exclusion.; Adsorbent characterization, operational parameters, and adsorbent recovery was studied.; Kinetics, isotherm models, and thermodynamics were evaluated.; The potential efficiency of adsorbent will also be checked for actual textile wastewater in future.;